Internet Gaming Disorder among High School Students at First Al-Karkh Education Directorate: The Prevalence and Consequences, Iraq - Meteab, Tawfeeq Qadri; Naji, Arkan Bahlol; Mahmoud , Aseel Ghazi (International Journal of Psychosocial Rehabilitation, 2020)
Recently, Internet Gaming Disorder (IGD) has been listed in the American Psychiatric Association, which suggests further research to explain this. Internet gaming disorder is the main issue of gaming. Methodology: A descriptive correlational study design carried out of the period from January 10th, 2020 to February 20th, 2020 to determine the internet gaming disorder among adolescents’ students: Prevalence and consequences at high Schools in first Al-Karkh education director, which the study carried out among (533) adolescents’ students selected by convenience sample from (8) high schools. The data collected by distribution of questionnaire composed of three parts (Socio demographic data, Internet gaming disorder scale and Health status of adolescent)The data collected after taken of the sample consent and data analyzed by using descriptive and inferential data analysis through using (SPSS). The results: show that mean of age is (16.93 ± 1.29), (51.4%) were male, (40.5%) at six grade, (56.3%) of them had good general health, the mean of time spent in video gaming is (1843.52 ± 4814.453) minutes, (75.4%) of them experience problematic gaming behavior, and (71.5%) of them had fair level of wellness. Discussion:There is a statistically significant positive correlation between IGT and each of psychological effects on health, emotional health effects, spiritual health effects, and overall wellness. There is a statistically significant difference in students’ IGTD among their self-described general health groups Conclusion: The study concluded that the student spent more time in playing video games, three quarter of students have experience problematic gaming behavior and the wellness of most students is classified as fair.Recommendations:The study recommends that training session for students about the side effect of electronic games, advise adolescents about social interaction with peers and family, the parent must provide emotional support for adolescents’ students and provide their needs, also take care of their children and monitoring them, and advise adolescents to decrease the time that spent in electronic game and using physical exercise .